1998
DOI: 10.1177/03635465980260050201
|View full text |Cite
|
Sign up to set email alerts
|

The Active Compression Test: A New and Effective Test for Diagnosing Labral Tears and Acromioclavicular Joint Abnormality

Abstract: Labral tears and acromioclavicular joint abnormalities were differentiated on physical examination using a new diagnostic test. The standing patient forward flexed the arm to 90 degrees with the elbow in full extension and then adducted the arm 10 degrees to 15 degrees medial to the sagittal plane of the body and internally rotated it so that the thumb pointed downward. The examiner, standing behind the patient, applied a uniform downward force to the arm. With the arm in the same position, the palm was then f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
324
4
10

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 547 publications
(340 citation statements)
references
References 4 publications
2
324
4
10
Order By: Relevance
“…I describe a new SAC test to identify AC joint involvement in anterior shoulder pain. It is a modification of the cross-body adduction test and active compressive test, as described by O'Brien et al 12 The SAC test was positive in all but 1 patient, giving it a sensitivity of 98% in my hands. It was found that weakness of resisted elevation in the test was a more prominent finding than pain, as presumably the pain limited the patient's ability to lift the arm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…I describe a new SAC test to identify AC joint involvement in anterior shoulder pain. It is a modification of the cross-body adduction test and active compressive test, as described by O'Brien et al 12 The SAC test was positive in all but 1 patient, giving it a sensitivity of 98% in my hands. It was found that weakness of resisted elevation in the test was a more prominent finding than pain, as presumably the pain limited the patient's ability to lift the arm.…”
Section: Discussionmentioning
confidence: 99%
“…All patients were examined, rotator cuff strength, 11 (graded from 0 to 5), impingement signs, AC joint testing, and palpation. The AC joint was clinically examined for local tenderness and 5 AC joint compressive tests were used in random order, including the cross-body adduction, 9 O'Brien's active compression test, 12 Paxinos test, 3 Jacob's test, 1 and the SAC test described below. Radiographs were ordered and assessed for signs of AC joint and erosion, congruency of the AC joint, and glenohumeral pathology.…”
Section: Methodsmentioning
confidence: 99%
“…We chose a homogeneous group for the assessments (Table 1), and all the athletes participated in similar categories. The only difference between the groups was the presence or the absence of pain during the tennis matches and during the irritative tests 18,19,20 that were performed by the first evaluator. In this context, we observed an average of 45 mm on the VAS in the dominant shoulder, which is more than the minimal clinically important difference in patients with shoulder disorders 28 .…”
Section: Discussionmentioning
confidence: 99%
“…They also could not report feeling pain in the following shoulder tests: Hawkins-Kennedy 18 , O'Brien 19 , and Shoulder Internal Impingement 20 . On the other hand, the subjects included in the PG all complained of dominant shoulder pain during and after the matches and also were required to have positive signs in the shoulder tests described above.…”
Section: Methods Subjectsmentioning
confidence: 97%
See 1 more Smart Citation